Extracorporeal Life Support in Hemorrhagic Conditions: A Systematic Review. Issue 5 (May 2021) - Willers, Anne; Swol, Justyna; Kowalewski, Mariusz; Raffa, Giuseppe Maria; Meani, Paolo; Jiritano, Federica; Matteucci, Matteo; Fina, Dario; Heuts, Samuel; Bidar, Elham; Natour, Ehsan; Sels, Jan Willem; et al.
Abstract : Extracorporeal life support (ECLS) is indicated in refractory acute respiratory or cardiac failure. According to the need for anticoagulation, bleeding conditions ( e.g., in trauma, pulmonary bleeding) have been considered a contraindication for the use of ECLS. However, there is increasing evidence for improved outcomes after ECLS support in hemorrhagic patients based on the benefits of hemodynamic support outweighing the increased risk of bleeding. We conducted a systematic literature search according to the PRISMA guidelines and reviewed publications describing ECLS support in hemorrhagic conditions. Seventy-four case reports, four case series, seven retrospective database observational studies, and one preliminary result of an ongoing study were reviewed. In total, 181 patients were identified in total of 86 manuscripts. The reports included patients suffering from bleeding caused by pulmonary hemorrhage (n = 53), trauma (n = 96), postpulmonary endarterectomy (n = 13), tracheal bleeding (n = 1), postpartum or cesarean delivery (n = 11), and intracranial hemorrhage (n = 7). Lower targeted titration of heparin infusion, heparin-free ECLS until coagulation is normalized, clamping of the endotracheal tube, and other ad hoc possibilities represent potential beneficial maneuvers in such conditions. Once the patient is cannulated and circulation restored, bleeding control surgery is performed for stabilization if indicated. The use of ECLS for temporary circulatory or respiratory support in critical patients with refractory hemorrhagic shock appears feasible considering tailored ECMO management strategies. Further investigation is needed to better elucidate the patient selection and ECLS management approaches. Abstract : Supplemental Digital Content is available in the text.